Amplitude analysis of B-→D+π-π- decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2016)
The Dalitz plot analysis technique is used to study the resonant substructures of B−→D+π−π− decays in a data sample corresponding to 3.0 fb−1 of pp collision data recorded by the LHCb experiment during 2011 and 2012. A model-independent analysis of the angular moments demonstrates the presence of resonances with spins 1, 2 and 3 at high D+π− mass. The data are fitted with an amplitude model composed of a quasi-model-independent function to describe the D+π− S wave together with virtual contributions from the D∗(2007)0 and B*0 states, and components corresponding to the D∗2(2460)0, D∗1(2680)0, D∗3(2760)0 and D∗2(3000)0 resonances. The masses and widths of these resonances are determined together with the branching fractions for their production in B−→D+π−π− decays. The D+π− S wave has phase motion consistent with that expected due to the presence of the D∗0(2400)0 state. These results constitute the first observations of the D∗3(2760)0 and D∗2(3000)0 resonances, with significances of 10σ and 6.6σ, respectively.